2019
DOI: 10.18632/aging.102150
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in heart failure is associated with altered Wnt signaling in the hippocampus

Abstract: Age represents the highest risk factor for death due to cardiovascular disease. Heart failure (HF) is the most common cardiovascular disease in elder population and it is associated with cognitive impairment (CI), diminishing learning and memory process affecting life quality and mortality in these patients. In HF, CI has been associated with inadequate O2 supply to the brain; however, an important subset of HF patients displays CI with almost no alteration in cerebral blood flow. Importantly, nothing is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 87 publications
(144 reference statements)
4
34
0
1
Order By: Relevance
“…Thus, the time-dependent differences in microglial derami cation and pro-in ammatory markers between the PVN and the amygdala are in line with the fact that sympathohumoral and cardiovascular manifestations in HF precede the mood and cognitive de cits associated with this disease (58,80,81). HF-induced cognitive impairments in both rats and mice has been previously described (82,83) and while it is well established that the PVN is a main neuronal substrate contributing to mood regulation, our studies provide an indirect evidence that neuroin ammation within the amygdala may constitute a neuronal substrate contributing to HF-induced mood de cits. A recent study showed that the microglia inhibitor minocycline improved depression-like behavior in HF rats (84).…”
Section: Discussionsupporting
confidence: 70%
“…Thus, the time-dependent differences in microglial derami cation and pro-in ammatory markers between the PVN and the amygdala are in line with the fact that sympathohumoral and cardiovascular manifestations in HF precede the mood and cognitive de cits associated with this disease (58,80,81). HF-induced cognitive impairments in both rats and mice has been previously described (82,83) and while it is well established that the PVN is a main neuronal substrate contributing to mood regulation, our studies provide an indirect evidence that neuroin ammation within the amygdala may constitute a neuronal substrate contributing to HF-induced mood de cits. A recent study showed that the microglia inhibitor minocycline improved depression-like behavior in HF rats (84).…”
Section: Discussionsupporting
confidence: 70%
“…As recalled in previous sections, both earlier and more recent reports indicate that GSK‐3β inhibitors can promote adult neurogenesis both under normal and injury conditions, either in vivo or in vitro. In vitro protocols that modulate Wnt signalling to improve cell therapies for PD are increasingly being developed (Arenas, ; Broski et al, ; Joksimovic & Awatrami, ; Kirkeby et al, , ; Kriks et al, ; Parish & Thompson, ; Prakash & Wurst, 2014; Toledo et al, ; Zhang et al, ). To date, a number of GSK‐3β‐antagonists have been described, some of which have been tested for their potential to promote adult neurogenesis (Table ).…”
Section: Therapeutic Modulation Of Wnt/β‐catenin Signallingmentioning
confidence: 99%
“…Particularly, we concentrated on the key pathway regulating DAergic neurogenesis, from neurodevelopment through aging and neurodegeneration: the wingless‐type mouse mammary tumor virus integration site (Wnt)/β‐catenin (WβC) signalling cascade (Brodski, Blaess, Partanen, & Prakash, ; Inestrosa & Arenas, ; Maiese, ; Maiese, Faqi, Chong, & Shang, ; Marchetti, ; Nusse & Clevers, ; Nusse & Varmus, ; Palomer et al, ; Salinas, ; Tapia‐Rojas & Inestrosa, ; Toledo et al, ; Wurst & Prakash, ). The WβC‐signalling pathway is of utmost importance owing to its ability to promote tissue repair and regeneration of stem cell activity in diverse organs, and in light of its crucial role in age‐related pathogenesis and therapy of disease (Banerjee, Jothimani, Prasad, Marotta, & Pathak, ; Garcìa, Udeh, Kalahasty, & Hackam, ; Garcìa‐Velasquez & Arias, ; Nusse & Clevers, ; Tauc & Jasper, ; Toledo et al, ). The hallmark of the WβC‐pathway is the activation of the transcriptional activity of β‐catenin, the pivotal mediator of the so‐called “ canonical ” Wnt signalling.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the time-dependent differences in microglial cell activation and pro-inflammatory markers between the PVN and the amygdala are in line with the fact sympathohumoral and cardiovascular manifestations in HF precede the mood and cognitive deficits associated with this disease (58,80,81). HF-induced cognitive impairments in both rats and mice have been extensively studied (82,83) and while it is well established that the PVN is a main neuronal substrate contributing to mood regulation, our studies provide an indirect evidence that NI within the amygdala may constitute a neuronal substrate contributing to HF-induced mood deficits. A recent study showed that the microglia inhibitor minocycline improved depression-like behavior in HF rats (84).…”
Section: Region-specific Differences and Time-dependency Of Heart Faimentioning
confidence: 65%